(untitled) (Global Journal of Management and Business Research, 2020)
The continued volatility of the Naira / USD exchange rate has attracted the attention of Nigeria’s Central Bank (CBN) to engage in the foreign exchange market. This study aims to examine the long-run relationship between interventions on the foreign exchange market and the Naira / USD exchange rate. Regarding four variables, the analysis uses annual data, namely the: Naira / USD exchange rate, money supply, net foreign assets, and interest rates from 1980-2018. This research also used non-linear unit root, cointegration and causality testing approach. The non-linear unit root tests for stationarity by KSS and Breitung showed that the variables employed were stationary at the first difference. Besides, nonlinear Breitung cointegration tests showed the existence of the long-term relationship between foreign market interventions and the Naira / USD exchange rate.